Fault modeling of general momentum exchange devices in spacecraft attitude control systems. Issue 11 (July 2020) - Yue, Chengfei; Shen, Qiang; Cao, Xibin; Wang, Feng; Goh, Cher Hiang; Lee, Tong Heng
Abstract: This paper investigates the mechanism of various faults in momentum exchange devices. These devices are modeled as a cascade electric motor (EM) - variable speed drive(VSD) system. Considering the mechanical part of the EM and the VSD system, potential faults are reviewed and summarized. Then, a general fault model in a cascade multiplicative structure is established for momentum exchange devices. Based on this general model, various fault scenarios can be simulated and tested, and the possible outputs affected by faults can be appropriately visualized. Specifically, six types of working condition are identified, and the corresponding fault models are constructed. Using these fault models, the control responses using reaction wheels and single gimbal control moment gyros under various fault conditions can be demonstrated. The simulation results show the severities of the faults and demonstrate that the additive fault is more serious than the multiplicative fault from the viewpoint of control accuracy. Finally, existing fault-tolerant control strategies are briefly summarized and potential approaches including both passive and active ones accommodating gimbal fault of single gimbal control moment gyro are demonstrated.